Long-term follow-up of pallidal Deep Brain Stimulation in teenagers with refractory Tourette syndrome and comorbid psychiatric disorders: About three cases. (January 2017) - Hauseux, P.-A.; Cyprien, F.; Cif, L.; Gonzalez, V.; Boulenger, J.-P.; Coubes, P.; Capdevielle, D.
Abstract: Objectives: Tourette syndrome (TS) is a complex neuropsychiatric disorder associated with comorbid psychiatric disorders. Peak of tic severity typically occurs in early adolescence and impacts quality of life. Since 1999, promising therapeutic effects of Deep Brain Stimulation (DBS) have been reported in tic reduction for adults with refractory TS. The aim of the study was to assess the long-term risk-benefit ratio of pallidal DBS for young patients with refractory TS and severe comorbid psychiatric disorders. Methods: We retrospectively assessed the long-term clinical outcomes of three adolescents who underwent pallidal DBS for the treatment of refractory TS. Results: The mean duration of follow-up was 52 months in our case series. We observed that motor tics decreased with posteroventral GPi DBS in all patients, without reaching a continuous significance over the long-term follow-up. Self-reported social inclusion was globally improved, despite lack of efficacy of DBS on comorbid conditions. Conclusions: These findings suggest a long-term therapeutic benefit of early DBS intervention for highly socially impaired young patients suffering from intractable TS with severe comorbid psychiatric conditions. Further studies are needed to determine the most effective targets of DBS on both tics and comorbid psychiatric profile of TS. Highlights: Tourette syndrome (TS) is characterized by tics typically beginning in childhood. Tourette syndrome is associated with a high rate of comorbid psychiatric disorders. In case of refractory symptoms, Deep Brain Stimulation (DBS) can be considered. A report of long-term DBS efficacy from three adolescents with severe TS is proposed. Multiple targeting is a research path in TS with comorbid psychiatric disorders.